A heuristic approach for accessing and employing the infrared behavior of Yang-Mills correlation functions - Machado, F. A. [UNESP]; Natale, A. A. [UNESP] (AIP Publishing, 2013)
This work analyses a hypothetically improved perturbative approach taking a dressed massive-like gluon propagator and an effective coupling into account. As an early step, corrections were calculated to the ghost and gluon propagators, and the ghost-gluon vertex in the Landau gauge, pure SU(3) Yang-Mills theory. Results were satisfactorily compared with lattice data. © 2013 American Institute of Physics.
Keywords: gluon mass; perturbative method